2013
DOI: 10.1007/jhep09(2013)057
|View full text |Cite
|
Sign up to set email alerts
|

Linear growth of entanglement entropy in holographic thermalization captured by horizon interiors and mutual information

Abstract: We study the holographic entanglement entropy in a homogeneous falling shell background, which is dual to the strongly coupled field theory following a global quench. For d=2 conformal field theories, it is known that the entropy has a linear growth regime if the scale of the entangling region is large. In addition, the growth rate approaches a constant when the scale increases. We demonstrate analytically that this behavior is directly related to the part of minimal area surface probing the interior of appare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 123 publications
3
20
0
Order By: Relevance
“…For example, in [8-14, 16, 50] it was found that after a global quench, an initial quadratic growth of entanglement with time is followed by a universal linear growth regime. The special case where the final state is an AdS-Schwarzschild black hole is referred to as entanglement tsunami [12][13][14]. Noteworthy, in [14] the linear growth is found to be independent of the choice of entangling regions.…”
Section: Jhep10(2017)034mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in [8-14, 16, 50] it was found that after a global quench, an initial quadratic growth of entanglement with time is followed by a universal linear growth regime. The special case where the final state is an AdS-Schwarzschild black hole is referred to as entanglement tsunami [12][13][14]. Noteworthy, in [14] the linear growth is found to be independent of the choice of entangling regions.…”
Section: Jhep10(2017)034mentioning
confidence: 99%
“…Then, these solutions are refined by using Newton's method that yields the solution with the desired accuracy, in our case fifteen digits. If more than one solution is regular in the sense that the length is positive, the final answer is taken to 13 Even upon expressing hyperbolic functions in terms of exponentials and changing variable from x to ξ = exp(Ax), the exponents of new the variable are non-integer for any choice of A.…”
Section: Numerical Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutual information has several advantages over entanglement entropy. In the context of holography, mutual information has been used extensively to study various aspects of quantum entanglement, for example see [8,[25][26][27][28][44][45][46][47][48][49].…”
Section: Mutual Information and Effective Temperaturementioning
confidence: 99%
“…The corresponding metric is given by (1.4). For example entanglement entropy has been studied in [23][24][25][26][27][28][29][30][31][32] and mutual information in [33][34][35][36]. Now it is natural to study the time-dependency of the holographic entanglement entropy and mutual information in time-dependent hyperscaling violating background.…”
Section: Jhep03(2016)202 2 Mutual Information In Hyperscaling Violatimentioning
confidence: 99%